Advances in scattering and biomedical engineering : (World Scientific, 2004)
This book contains papers on scattering theory and biomedical engineering - two rapidly evolving fields which have a considerable impact on today's research. All the papers are state-of-the-art, have been carefully reviewed before publication and the authors are well-known in the scientific community. In addition, some papers focus more on applied mathematics, which is the solid ground for development and innovative research in scattering and biomedical engineering.